Development of A Prototype Book Based on The Study of The Al-Quran as Teaching Material For Physics - Azmar Azmar; Lalu Usman Ali (Jurnal Pendidikan Fisika, 2022)
Integration of the spiritual values and knowledge of students which are summarized into a learning outcome becomes the focus in the development of physics teaching materials based on Al-Qur'an studies with the main objectives: (1) to design a valid physics teaching materials based on Al-Qur'an studies at Madrasah Aliah, (2) to analyze the practicality of physics teaching materials based on Al-Qur'an studies at Madrasah Aliah, and (3) to analyze the effectiveness of physics teaching materials based on Al-Qur'an studies at Madrasah Aliah. The research design used was 4D Model (Definition, Design, Development and Deployment). The sample in its implementation was at MAN 3 Mataram. The technique analysis used were Validity Analysis, Practicality Analysis, and Effectiveness Analysis. The percentage of classical mastery of the students was 76.92% which was categorized as good. Thus, according to the theory put forward by J. Van Den Akker, that the teaching materials have been operationally effective to provide learning outcomes as expected. The results of these tests indicate that the development of teaching materials based on the study of the Qur'anic science is very effective in achieving students’ learning outcomes as a form of mastery in learning. In concusion, the overall teaching materials in the development of the prototype book as physics teaching materials based on al-qur'an studies for Madrasah Aliyah Students can support students’ learning achievement both in the cognitive aspects and more specifically in the knowledge and spiritual aspects.